WSUD engineering procedures stormwater - Allison, Robin; Francey, Matt (CSIRO : Melbourne Water, 2005)
Practical engineering solutions to those who need to implement WSUD.
Keywords: Waterworks -- Australia -- Victoria -- Design and construction.; Water-supply engineering.; Storm sewers -- Australia -- Victoria.; Urban runoff -- Australia -- Victoria.; Water quality management -- Australia -- Victoria.; Water conservation -- Australia -- Victoria.; Urban hydrology -- Australia -- Victoria.; Victoria.; elektronické knihy; electronic books